Effectiveness of Logotherapy on the Organization-Based Self-Esteem and Job Satisfaction of Employed Midwives - Farahnaz Bazargan-Sabet; Katayoun Alidousti; Anahita Tashk; Vahid Yazdi-Feyzabadi; Atefeh Ahmadi (Wolters Kluwer Medknow Publications, 2024)
Background: Midwives as one of the most effective members of the health systems play a key role in delivering health services to mothers and children who are vulnerable groups of the society. This research aimed to investigate the effect of Logotherapy on job satisfaction and Organization-Based Self-Esteem (OBSE) of employed midwives. Materials and Methods: This is a quasi-experimental study with the pretest and posttest design and a control group from all midwives employed in the public hospital of Rasht City in Iran. Fifty-six midwives fulfilling the inclusion criteria were selected and randomly divided into two groups of intervention and control. They filled job satisfaction, OBSE questionnaires, and demographic information checklist, and then, the intervention group attended Logotherapy for six sessions/90 minutes. Finally, both groups answered the instruments as posttest. Results: Results showed that the mean difference between OBSE (F 6,83 = 27, p < 0.05) and job satisfaction (t 2,62 = 27, p < 0.01) scores before and after the sessions in the intervention group was significantly more than the control group. Conclusions: Group Logotherapy increased job satisfaction and OBSE among midwives. It can be recommended for use in the clinical settings for healthcare providers.